2017
DOI: 10.1155/2017/8369737
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transcutaneous Electrical Acupoint Stimulation on Inflammatory Response in Patients Undergoing Limb Ischemia-Reperfusion

Abstract: Reperfusion after tourniquet use can induce inflammation and cause remote organ injury. We evaluated the therapeutic effect of transcutaneous electrical acupoint stimulation (TEAS) on inflammatory mediators and lung function in patients receiving lower limb tourniquets. Forty patients undergoing unilateral lower extremity surgery with tourniquet were randomly assigned to two groups: the TEAS group and ischemia-reperfusion (I/R) group. The C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligand 8 (CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Our result is in line with previous studies showing that transcutaneous electrical acupoint stimulation (TEAS) diminished the upregulation of pro-inflammatory factors in response to lower limb ischemiareperfusion in patients undergoing limb ischemia-reperfusion [29]. Moreover, in animal experimental studies it has been shown that acupuncture intervention have positive roles in relieving inflammatory reaction in rheumatoid arthritis by suppressing myocardial inflammatory cytokines (suppressing TNFα, IL-8, etc.…”
Section: Safetysupporting
confidence: 92%
“…Our result is in line with previous studies showing that transcutaneous electrical acupoint stimulation (TEAS) diminished the upregulation of pro-inflammatory factors in response to lower limb ischemiareperfusion in patients undergoing limb ischemia-reperfusion [29]. Moreover, in animal experimental studies it has been shown that acupuncture intervention have positive roles in relieving inflammatory reaction in rheumatoid arthritis by suppressing myocardial inflammatory cytokines (suppressing TNFα, IL-8, etc.…”
Section: Safetysupporting
confidence: 92%
“…ST36 and SP6 are two main anti-inflammatory EA points. Our previous clinical studies demonstrated that transcutaneous electrical acupoint stimulation at the ST36 and SP6 acupoints could inhibit the inflammatory response in the patients undergoing limb ischemia-reperfusion (33). Torres-rosas et al (34) also revealed that EA pre-treatment at these acupoints could inhibit inflammation in a murine model of sepsis established by cecal ligation and puncture or lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 95%
“…Our result is in line with previous studies showing that transcutaneous electrical acupoint stimulation (TEAS) diminished the upregulation of pro-inflammatory factors in response to lower limb ischemia-reperfusion in patients undergoing limb ischemia-reperfusion. 29 Moreover, in animal experimental studies it has been shown that acupuncture intervention has positive roles in relieving inflammatory reaction in rheumatoid arthritis by suppressing myocardial inflammatory cytokines (suppressing TNF-α, IL-8, etc. ), adjusting inflammatory reaction pathway.…”
Section: Discussionmentioning
confidence: 99%